Unmasking the psychological impact of the early COVID-19 pandemic in young adults: results from a cross-sectional online survey - Shazley, Omar; Wiciak, Michelle Teresa; Santhosh, Daphne (Frontiers in Psychiatry, 2025)
BackgroundThe COVID-19 pandemic emerged as an international public health emergency and threat to individual psychological resilience.ObjectiveTo examine the prevalence of psychological issues and identify key associations with mental health indicators in young adults (ages 18-28) worldwide during the initial phase of the pandemic.MethodsThrough a cross-sectional online survey utilizing convenience sampling, we collected data on demographics, COVID-19-related questions, depression (Patient Health Questionnaire-9), anxiety (Generalized Anxiety Disorder-7), stress/trauma (Impact of Event Scale-Revised), and fear of COVID-19 (Fear of COVID-19 scale) between September 2020-January 2021. A total of 183 were eligible analysis. All statistical analyses were set at alpha = 0.05.ResultsOver 70% of participants reported mild anxiety (n=129), 80% mild depression (n=136), 40% pandemic-related trauma (n=61), and 50% high fear (n=88). Female respondents reported higher anxiety (t(173)=-3.352, <.001), depression (t(166)=-3.310, P=.001), and trauma from COVID-19 ((t(151)=-2.004, P=.047). Hispanic/Latino/a/x participants reported higher depression (F(2,156)=7.761, P<.001) and trauma scores (F(2,143)=3.999, P=.020). Age in 2020 was associated with trauma total scores (F(1,154)=4.230, P=0.041, R2 = 0.027). Individuals who were mandated a quarantine were linked to lower levels of anxiety (F(2,175)=3.442, P=.034) and depression (F(2,170)=3.092, P =.048) than those not mandated. Those quarantined with close contacts were linked to lower anxiety (t(162.184)=2.705, P =.008) and trauma (t(149)=2.169; P=.032). Close contacts’ hospitalization from COVID-19 infections were linked to lower anxiety (t(127)=2.855, P=.005), depression(t(123)=3.111, P=.002), and trauma (t(152)=-1.975, P=.050).ConclusionThe findings highlight the significant effect COVID-19 had on mental health in young adults worldwide.